Estudo in vitro da infectividade de espécies de Leishmania do subgênero Viannia em macrófagos peritoneais de camundongo BALB/c - CAMPOS, Marliane Batista (Universidade Federal do Pará, 2013)
Parasites ofthe genus Leishmania show both intra- and inter-specific variations of infectivity. There is little available information, however, regarding the infective behavior of New World species particularly those of the Amazon Region of Brazil, where there occur at six species of the subgenus Viannia causing human cutaneous leishmaniasis (ACL). The aim of the present study was to investigate the infectivity of 5 of these species for the peritoneal macrophages of BALB/c mice, and their role in the host-cell's production of nitric oxide (NO). Thirty strains of Leishmania were divided into 6 groups of the fol1owing species: I-L. (V.) braziliensis (from cases of localized skin lesions-LCL); II- L. (V.) braziliensis (from cases of mucocutaneous lesions- LeM); III- L. (V.) guyanensis; IV- L. (V.) shawi; V- L. (V.) naiffi and VI- L. (V.) lainsoni. They were cultivated in RPMI 1640 medium supplemented with 10% fetal bovine serum and 1% penicillin/gentamicin, until reaching the stationary phase of development. These promastigotes were used to infect the macrophage cell cultures, in the proportion of 4 flagellates/macrophage. The cultures were then incubated at 35°C with 5% CO2 and, after 24 hours following inoculation, the corvelips were stained by Giemsa's method to determine the infection index. The nitric oxide (nitrite) concentration was measured in the culture supernatant by Griess' s method to determine the infection index. The nitric oxide (nitrite) concentration was measured in the culture supernatant by Griess' s method. It was found that LCM strains of L. (V.) braziliensis showed the highest infection index (385), significance p<0.05,compared with L. (V.) braziliensis LCL strains (264). L. (V). naiffi and L. (V.) lansoni had the lowest infection indices of (215) and (272), respectively, but, were not significally different from index of L. (V.) guyanensis (300). Rrgarding the NO levels, the highest was that for L. (V.) naiffi (4,1µM), and the lowest for L. (V.) braziliensis-LCM strains (2, 15µM). The other readings were (3,14µM) for L. (V.) lainsoni, 2,96µM for L. (V.) shawi, 2,76µM for L. (V.) guyanensis and 3,1µM for L. (V.) braziliensis-LCL strains. It is conc1uded that L. (V.) natffi. In this way it may be noted the NO levels for infected macrophage were inversely proportional to the degree of infectivity of the species studied.